A New Species of Petasites Gaertn. (Compositae) from India - Deb, D. B. (Indian Forester, 1967)
Petasites kamengicus Deb, spec. nov. (Compositae) collected from Kameng Frontier Division of North East Frontier Agency, India. Is described with illustration.